ORGANIZATION AND IMPLEMENTATION OF ONLINE LANGUAGE AND ONLINE LITERARY COURSE AT FACULTIES AND SECONDARY SCHOOLS IN SERBIA (Heritage, 2021)
The aim of this paper is to determine the ways in which the online language and literature courses had been conducted in secondary schools (and high schools) and faculties across Serbia, when the pandemics caused by the appearance of coronavirus forced all educational institutions worldwide to abandon the traditional way of teaching and adopt the new teaching practices which took place in virtual environments. One of the key issues explored in this paper is whether the language and literature teachers in Serbia had been provided with enough teacher training regarding the use of online platforms and online tools, as well as whether they had had previous experience in an online course design, its organisation and realization. The paper examines the following hypotheses: it is assumed that the concept of distance learning in Serbia has not come to fruition (1) and that the lack of digital literacy of both teachers and students is the result of the country’s poor development of e-Learning, as well as the lack of suitable teacher training systems that would provide teachers with practical knowledge in regard with dealing with online platforms and proper use and application of the most innovative digital tools (2). The obtained results have confirmed the hypotheses set up in the paper. The results point to the need for conducting further research into this field, in particular, when it comes to proper organization of online language courses as well as the redifiniton of the goals and methodologies established in online language courses. Moreover, the results stress an urgent need for designing and implementation of an entirely new concept in Serbia – an online literature course model – that has not been explored yet and that calls for an immediate research into the field of literature and the methodology of teaching literature.
Keywords: distance education, digital tools, online literature course, online language course, language and literature teachers.